THE ROLE OF THE VILLAGE GOVERNMENT IN DISTRIBUTING SOCIAL ASSISTANCE TO THE COMMUNITY IN MEDAN ESTATE VILLAGE, PERCUT SEI TUAN DISTRICT - Saragih, Theresia; Hasibuan, Rizal Sanusi; Panjaitan, Novia Adeliana; Julia Ivanna (Politea : Jurnal Politik Islam, 2024)
The purpose of this study is to find out the role of the village government in distributing social assistance, the obstacles faced and the efforts made by the Medan Estate village government in distributing social assistance to villagers. The method used in this study is a qualitative method with a descriptive type of research. The collected data is then grouped and analyzed based on the similarity of the data type with the aim of drawing conclusions from the data obtained. From this study, it can be concluded that the role of the Medan Estate Village government in distributing social assistance is to collaborate with all village officials and the obstacle in distributing this assistance is the many envy of fellow residents and the efforts made by the village community. The goal of the village government in distributing social assistance is to establish good communication with the community so that programs at the village level can run smoothly.